Sugar-sweetened beverages consumption in a multi-ethnic population of middle-aged men and association with sociodemographic variables and obesity - AlFaris, Nora A.; Alshwaiyat, Naseem M.; Alkhalidy, Hana; AlTamimi, Jozaa Z.; Alagal, Reham I.; Alsaikan, Reem A.; Alsemari, Malak A.; BinMowyna, Mona N.; AlKehayez, Nora M. (Frontiers in Nutrition, 2022)
Background: Adults frequently consume sugar-sweetened beverages. These products are linked to negative health effects such as obesity. Our study was carried out to assess rates of weekly and daily sugar-sweetened beverages consumption in a multi-ethnic population of middle-aged men and association with sociodemographic variables and obesity. Methods: A sum of 1800 middle-aged men (36-59 years) living in Riyadh, KSA, participated in this cross-sectional study. Sociodemographic variables and the frequency of sugar-sweetened beverages consumption were gathered from participants using face to face interviews. Weekly and daily consumption of sugar-sweetened beverages were the two binary outcome variables applied in this research. Weight and height were measured following standard procedures. Results: In this study, 93.8 % and 32.6 % of participants consumed sugar-sweetened beverages weekly and daily, respectively. The weekly and daily sugar-sweetened beverages consumption was predicted by nationality. Subjects from Pakistan (99.3%) and Yemen (60.0%) reported the greatest rates of weekly and daily consumption, respectively, while Bangladeshi and Sudanese subjects reported the lowest rates of weekly (87%) and daily (2.9%) consumption, respectively. Another factor that predicted weekly sugar-sweetened beverages consumption was obesity. Obese subjects had a significantly greater odds ratio of weekly sugar-sweetened beverages intake than non-obese individuals (OR = 3.80, P = 0.003). Conclusion: Consumption of sugar-sweetened beverages is common among middle-aged men who live in KSA. Results show connecting sugar-sweetened beverages intake with specific sociodemographic variables and obesity.